2016
DOI: 10.1002/admi.201600117
|View full text |Cite|
|
Sign up to set email alerts
|

Moisture and Oxygen Enhance Conductivity of LiTFSI‐Doped Spiro‐MeOTAD Hole Transport Layer in Perovskite Solar Cells

Abstract: pinholes with an average diameter of ≈135 nm. These pinholes form channels that wiggle within the spiro-MeOTAD fi lm, and are thought to accelerate diffusion of gas molecules from ambient air (e.g., H 2 O and O 2 ) into the perovskite layer in perovskite-based solar cells. [ 8c ] They also facilitate the outward diffusion of chemical elements/compounds, such as LiTFSI, which is hygroscopic. Therefore, ambient air exposure results in a re-distribution of LiTFSI dopants across the spiro-MeOTAD fi lm. [ 8c ] Ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
155
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(172 citation statements)
references
References 50 publications
(44 reference statements)
8
155
1
Order By: Relevance
“…While the PCEs of the MAPbI 3 (AS) devices decreased to 90% of their initial performance after approximately 300 h. An initial increase of PCEs for both samples is observed in the first 20 h of the stability test. A similar phenomenon was also observed previously 55,62 , and was ascribed to the effects such as elevated temperature (approximately 46 °C), light or field induced ion movement, light-induced traps formation, interfacial charge accumulation 55 , or spiro-OMeTAD conductivity variation 63 . In addition, both devices showed a fast, exponential decay region after reaching the highest performance points, which is followed by a slower linear decay 64 .…”
Section: Resultssupporting
confidence: 84%
“…While the PCEs of the MAPbI 3 (AS) devices decreased to 90% of their initial performance after approximately 300 h. An initial increase of PCEs for both samples is observed in the first 20 h of the stability test. A similar phenomenon was also observed previously 55,62 , and was ascribed to the effects such as elevated temperature (approximately 46 °C), light or field induced ion movement, light-induced traps formation, interfacial charge accumulation 55 , or spiro-OMeTAD conductivity variation 63 . In addition, both devices showed a fast, exponential decay region after reaching the highest performance points, which is followed by a slower linear decay 64 .…”
Section: Resultssupporting
confidence: 84%
“…[35][36][37] Conings et al [28] found significant MAPbI 3Àx Cl x degradation at 85 8C, even under inert conditions. [40] On the other hand, spiro-OMeTAD [35,36,41,42] tends to crystallize owing to segregation of the lithium bis-trifluoromethanesulfonimide (LiTFSI) additive under air exposure, inducing pinholes in the film, [43] which can negativelya ffect the contact between the perovskite and the HTL. [38] On one hand, strategies to improve the stabilityo ft he perovskite activel ayer could be the replacement of MAPbI 3 with am ixed halide MAPbI 3Àx Br x with large bandgap [39] or the substitutiono fM A + with formamidinium (FA + ), for the realization of FAPbI 3 perovskite film.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, inclusion of these two components signifies a major bottleneck toward low‐cost commercialization, as their preparation requires expensive purification processes and they exhibit poor long‐term stability . Furthermore, to overcome poor material conductivity and hole mobility, lithium and/or cobalt salts are usually incorporated into the film, which has a detrimental effect on device stability normally attributed to their reactivity and highly hygroscopic behavior. Therefore, despite their remarkable power conversion efficiency, PSC commercialization is hindered by the use of expensive hole‐transport materials and poor device stability.…”
Section: Introductionmentioning
confidence: 99%